Role of School Management Committees in Promoting Elementary Education in Tribal Concentrated Areas in Meghalaya State : A Perspective Analysis - Tyagi, Ankur; Singh, Ayushui; Singh, Virendra Pratap (JOURNAL OF INDIAN EDUCATION, 2023)
The crux of this paper is to analyse the role of School Management Committees (SMCs) in promoting elementary education in tribal concentrated areas based on a field study in Meghalaya state. This study is based on the schedules used for data collection and Focus Group Discussions (FGDs) held with the community members about the source of funds, management of funds, activities for school development plans, receipt of complaints and nature thereof, women participation, and specific actions taken on the school enrolment. The findings in this paper reflect a positive and motivating trend about the community’s role in promoting elementary school education. However, to attain the constitutional provisions, public policies and programmes on the effective role of the community, especially in empowering the SMCs, more stringent measures should be taken uniformly, in a letter and in spirit.